Check the placeEmergency resection or diverting stoma followed by elective resection in patients with colonic obstruction due to locally advanced cancer: a national cohort study. (16th July 2021) - Rosander, Emma; Holm, Torbjörn; Sjövall, Annika; Hjern, Fredrik; Weibull, Caroline E.; Nordenvall, Caroline
Abstract: Aim: The aim was to assess long‐term prognosis after emergency resection versus primary diverting stoma followed by elective tumour resection. Method: A national‐register‐based cohort study with retrospective analysis of prospectively collected data was performed. All Swedish patients with non‐metastatic obstructive locally advanced colon cancer treated with emergency resection or diverting stoma, followed by an elective resection, between 2007 and 2017 were included. The Kaplan–Meier method and Cox proportional hazards model were used to compare all‐cause mortality between patients with emergency resection and elective right‐ and left‐sided resection. The multivariable model was adjusted for year of diagnosis, age at diagnosis, sex, Charlson Comorbidity Index, American Society of Anesthesiologists class, tumour location and pN stage. Results: In all, 751 patients with a tumour in the right colon and 700 patients with a tumour in the left colon were included. Emergency resection was more common in patients with right‐sided colon tumours (681/751) than in patients with left‐sided colon tumours (483/700). The 5‐year overall survival in patients with right‐sided tumours was 25% after emergency resection and 46% after diverting stoma followed by elective resection (log‐rank test P  = 0.001). The corresponding numbers for patients with left‐sided colon tumours were 40% and 64% ( P  < 0.001). Emergency resection was independently associated with increased all‐cause mortality in patients with left‐sided tumour (hazard ratio 1.63, 95% CI 1.21–2.19) but not in patients with right‐sided tumour (hazard ratio 1.21, 95% CI 0.80–1.81). Conclusion: Diverting stoma followed by elective resection is associated with improved survival compared with emergency resection in patients with left‐sided colonic obstruction due to locally advanced tumours.